2012
DOI: 10.1111/j.1440-1584.2012.01268.x
|View full text |Cite
|
Sign up to set email alerts
|

The benefits of a tailor‐made pilot primary health‐care course for Indigenous high school students in remote Queensland

Abstract: This study demonstrates that a tailor-made primary health-care education course can create opportunities for Indigenous people to pursue health careers, promote health knowledge and leadership skills, inspire pride and self-esteem, and strengthen links within the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…The literature comprised three distinct institutional categories: six publications primarily examined university led aspiration and/or outreach programs targeting secondary school students (Godinho, Wooley, Webb, & Winkel, 2015;Peralta, Cinelli, & Bennie, 2018;Shinkfield, 2014;Smith et al, 2015;Thomas, Bronwyn, Kirkham, & Parry, 2014;Thorn & Flodin, 2015); two publications focused on vocational education and training (VET) programs based at secondary schools (Oliver, Grote, Roschecouste, & Exell, 2013;Pham, Page, Sivamalai, & Woolley, 2012); and four related to experiential place-based learning programs with a local employment focus (Altman & Fogarty, 2010;Fogarty, 2012;Fogarty & Schwab, 2012;Kral, 2010). Ten publications reported studies conducted with students enrolled in community-based schools (Altman & Fogarty, 2010;Burton & Osborne, 2014;Fogarty, 2012;Fogarty & Schwab, 2012;Godinho et al, 2015;Kral, 2010;Peralta et al, 2018;Osborne et al, 2017;Smith et al, 2015;Thomas et al, 2014), and four publications reported studies conducted with remote Indigenous students who attended boarding schools (Oliver et al, 2013;Pham et al, 2012;Shinkfield, 2014;Thorn & Flodin, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The literature comprised three distinct institutional categories: six publications primarily examined university led aspiration and/or outreach programs targeting secondary school students (Godinho, Wooley, Webb, & Winkel, 2015;Peralta, Cinelli, & Bennie, 2018;Shinkfield, 2014;Smith et al, 2015;Thomas, Bronwyn, Kirkham, & Parry, 2014;Thorn & Flodin, 2015); two publications focused on vocational education and training (VET) programs based at secondary schools (Oliver, Grote, Roschecouste, & Exell, 2013;Pham, Page, Sivamalai, & Woolley, 2012); and four related to experiential place-based learning programs with a local employment focus (Altman & Fogarty, 2010;Fogarty, 2012;Fogarty & Schwab, 2012;Kral, 2010). Ten publications reported studies conducted with students enrolled in community-based schools (Altman & Fogarty, 2010;Burton & Osborne, 2014;Fogarty, 2012;Fogarty & Schwab, 2012;Godinho et al, 2015;Kral, 2010;Peralta et al, 2018;Osborne et al, 2017;Smith et al, 2015;Thomas et al, 2014), and four publications reported studies conducted with remote Indigenous students who attended boarding schools (Oliver et al, 2013;Pham et al, 2012;Shinkfield, 2014;Thorn & Flodin, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…They noted that task-based teaching and learning is effective in second language and literacy teaching for Indigenous students who struggle with the literacy and numeracy demands of VET courses. Furthermore, Oliver et al (2013) and Pham et al (2012) suggested that gaining qualifications during the secondary school phase of learning was beneficial to pursuing post-schooling pathways in various fields of study. For example, Pham et al (2012) described the benefits of a tailor-made primary health-care program.…”
Section: Task-based Learning While At Schoolmentioning
confidence: 99%
“…This study was limited to 9 caregivers (8 parents and 1 grandparent) which is a small sample size even for qualitative in-depth interview work but similar to other work in small, remote, north Australian communities [ 48 ]. The sample size represents approximately half of the population of parent generation in the remote community, and the parents were an information-rich source as a key stakeholder group for the detailed understanding of this case [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reported in the literature is a range of health workforce development initiatives targeting youth in regional, rural and remote settings. Australian examples include three health career development programs in Queensland [11][12][13] and one in South Australia 14 . International examples include a medicinefocused transition program for secondary school leavers in Ireland 15 and an outreach program in Canada 16 .…”
Section: Introductionmentioning
confidence: 99%
“…International examples include a medicinefocused transition program for secondary school leavers in Ireland 15 and an outreach program in Canada 16 . Although these programs have varied in format, duration, frequency and in the nature of learning activities utilised, all have been associated with positive outcomes for participants such as enhanced health literacy, increased awareness of health career choices and intentions to undertake higher and adult education 11,[14][15][16] . Longitudinal programs in particular were shown to enhance participants' self-esteem and confidence 13 and were associated with positive long-term impact 12 .…”
Section: Introductionmentioning
confidence: 99%